Environmental modelling of building stocks – An integrated review of life cycle-based assessment models to support EU policy making. (November 2021) - Röck, Martin; Baldereschi, Elena; Verellen, Evelien; Passer, Alexander; Sala, Serenella; Allacker, Karen
Abstract: Various environmental challenges, particularly the rising severity of the impacts of climate change, require a systematic shift in and decarbonization of the global economy. Due to their high environmental impacts, buildings and construction have a special role in decarbonization. Environmental modelling of building stock dynamics can help policy makers and inform decision making. This study presents a systematic review of both the latest scientific literature on environmental modelling of building stocks and related EU policy initiatives. Our findings illuminate the strengths and limitations of existing approaches as well as the potential of such modelling and the required directions for future development to provide effective policy support. Based on the assessment of 104 scientific papers, our study shortlisted and analysed 22 environmental building stock modelling approaches. While promising, these show various limitations on their effectiveness in supporting decarbonization efforts while avoiding burden shifting. Future building stock models should offer extended system boundaries and comprehensive life cycle assessment, improved hotspot analysis and impact monitoring across spatiotemporal scales. A long-term perspective on the entire building stock covering climate and other environmental impacts is needed, as outlined in the latest standards. By linking existing studies to related EU policy objectives, we identify various studies that investigate scenarios and strategies relevant to EU policy makers and highlight research gaps. Future research should enable comprehensive environmental assessment of building stocks across scales and emphasize the monitoring of multiple environmental impacts of building stock development to ensure compliance with environmental targets and minimization of trade-offs. Graphical abstract: Image 1 Highlights: Integrated review of EU policy documents and latest approaches for environmental modelling of building stocks. We analyse scope, methods, tools and data to find existing studies mostly focus on housing stock and on short to medium time horizons. Existing studies are limited in the number of archetypes, as well as coverage of building parts, life cycle stages and environmental indicators. The scope and level of detail of existing models hence require elaboration to effectively support EU policy for decarbonization of building operation and construction. Future research is particularly needed on environmental hotspot analysis and monitoring of impacts across time and space.